The Use of Coercive Interventions in Mental Health Care in Germany and the Netherlands. A Comparison of the Developments in Two Neighboring Countries - Steinert, Tilman; Noorthoorn, Eric O.; Mulder, Cornelis L. (Frontiers in Public Health, 2014)
In this review we compare the use of coercion in mental health care in Germany and in the Netherlands. Legal frameworks and published data on involuntary commitment, involuntary medication, seclusion, and restraint are highlighted as well as the role of guidelines, training and attitudes held by psychiatrists and the public. Legal procedures regulating involuntary admission and commitment are rather similar, and so is the percentage of involuntary admissions and the rate per 100.000 inhabitants. However, opposing trends can be observed in the use of coercive interventions during treatment which in both countries are considered as a last resort after all other alternative approaches have failed. In the Netherlands, for a long time seclusion has been considered as preferred intervention while the use of medication by force was widely disapproved as being unnecessarily invasive. However, after increasing evidence showed that number and duration of seclusions as well as the number of aggressive incidents per admission were considerably higher than in other European countries, attitudes changed within recent years. A national programme with spending of 15 million € was launched to reduce the use of seclusion, while the use of medication was facilitated. A legislation is scheduled which will allow also outpatient coercive treatment. In Germany, the latter was never legalized. While coercive treatment in Germany was rather common for involuntarily committed patients and mechanical restraint was preferred to seclusion in most hospital as a containment measure, the decisions of the Constitutional Court in 2011 had a high impact on legislation, attitudes and clinical practice. Though since 2013 coercive medication is approvable again under strict conditions, it is now widely perceived as very invasive and last resort. There is evidence that this change of attitudes lead to a considerable increase of the use of seclusion and restraint for some patients.